Norma jurídica, irretroatividade tributária e alterações jurisprudenciais - Santos, Aline Nunes dos (2009)
The scope of irretroactivity as a limitation to the construction of norms is discussed. This work aims to establish a standard definition of norm based on the structuring theory of Friedrich Müller. Assuming syntactic uniformity of law, it seeks to adapt elements proposed by Müller to the levy tax rule of Paulo de Barros Carvalho. The research analyses the meaning of tax irretroactivity on traditional and contemporary doctrine. It is proposed to apply the irretroactivity to the idea of norm. Finally, the work analyses the process of judicial rulemaking as well as the influence of tax irretroactivity in cases of overrulings